Principle, praxis, and the politics of educational reform in Meiji Japan - Lincicome, Mark Elwood, 1953- (University of Hawaii Press, 1995)
Scholars of modern Japan agree that education played a crucial role in that country's rapid modernization during the Meiji period (1868-1912). With few exceptions, however, Western approaches to the subject treat education as an instrument of change controlled by the Meiji political and intellectual elite. Principle, Praxis, and the Politics of Educational Reform in Meiji Japan offers a corrective to this view. By introducing primary source materials (including teaching manuals, educational periodicals, and primary school textbooks) missing from most English-language works, Mark Lincicome examines an early case of resistance to government control that developed within the community of professional educators. He focuses on what began, in 1872, as an attempt by the newly established Ministry of Education to train a corps of professional teachers that could "civilize and enlighten" the masses in compulsory primary schools. Through the Tokyo Normal School and other new teacher training schools sponsored by the government, the ministry began what it thought was a straightforward "technology transfer" of the latest teaching methods and materials from the United States and Europe. Little did the ministry realize that it was planting the seeds of broader reform that would challenge not only its underlying doctrine of education, but its very authority over education. The reform movement centered around efforts to explicate and disseminate the doctrine of kaihatsushugi (developmental education). Hailed as a modern, scientific approach to child education, it rejected rote memorization and passive learning, elements of the so-called method of "pouring in" (chunyu) knowledge practiced during thepreceding Tokugawa period, and sought instead to cultivate the unique, innate abilities of each child. Orthodox ideas of "education", "knowledge", and the process by which children learn were challenged. The position and responsibilities of the teacher were enhanced, consequently providing educators with a claim to professional authority and autonomy - at a time when the Meiji state was attempting to control every facet of the Japanese school system. Principle, Praxis, and the Politics of Educational Reform in Meiji Japan analyzes a key element to understanding Meiji development and modern Japan as a whole